Corporate Social Responsibility and financial performance: Evidence in Indonesia (basic industry and chemical sector) - Istiyanto, Choirul; Risfandy, Tastaftiyan; Andriansa, Rama (Proceeding of National Conference on Accounting & Finance, 2024)
Research on corporate social responsibility on financial performance has had various results. Differences in models, objects and several other supporting variables add to the uniqueness of CSR research on financial performance. This research uses a sample of manufacturing companies in the basic industrial and chemical sectors listed on the IDX in 2019-2022. Using Tobin's Q as a measure of financial performance and using the KLD method as a CSR measurement.